Seismic isolation as an alternative seismic upgrading scheme for Philippine bridges - Samson, Rafael Angelo G.
The Philippines is an earthquake-prone country, which is why Philippine bridges are exposed to a high level of earthquake risk. Earthquake mitigation measures here in the Philippines lag vis-a-vis the technologies being used worldwide. One of the most popular and leading technology in bridge engineering is the use of seismic isolators. In this research, seismic isolation is evaluated as an alternative seismic upgrading scheme for Philippine bridges. Evaluation was based on the effects of the seismic isolators on the seismic forces on the bridge pier. It was compared with the conventional upgrading scheme that currently being applied in Philippine bridges. Three types of isolators were analyzed, lead rubber bearing (LRB), high damping rubber bearing (HDRB) and natural rubber bearing with danlper (NRB). The HDRB brought the highest decrease in shear force and bending moment of the pier with 41% and 47% reduction respectively, followed by the LRB with 31 % and 39% reduction respectively and the NRB with 28% and 37% reduction respectively. The maximum displacement brought by the three seismic isolators is 259 mm which is well within the allowable isolator displacement of 600 mm. The conventional upgrade scheme applied to the bridge is Aramid Fiber Reinforced Polymer wrapping to the piers, which brought 14% reduction on the deck displacements. The main difference of the use of seismic isolator as an alternative seismic upgrading scheme is that it reduces the seismic forces being carried by the bridge members unlike the conventional upgrade scheme which relies directly to tile strengthening and stiffening of the members.